Impact of a multilevel HIV prevention programme on adolescent girls and young women's empowerment for risk reduction: A mixed methods evaluation in Kenya. - Elizabeth Kemigisha; Jane Osindo; Vivienne Kamire; Venetia Baker; Annabelle Gourlay; Stephen Gakuo; Sarah Mulwa; Faith Magut; Thomas Gachie; Moses Otieno; Sammy Khagayi; Daniel Kwaro; et al. (PLOS Global Public Health, 2025)
Empowerment is key to person-centered HIV prevention. This study aims to evaluate the extent to which the Determined, Resilient, Empowered, AIDS-free, Mentored, Safe (DREAMS) Partnership promotes empowerment of adolescent girls and young women (AGYW) in Kenya. We conducted a mixed-methods study to examine DREAMS influence on empowerment precursors (resources, agency, institutional structures) and outcomes, guided by Kabeer's framework for women's empowerment. With representative cohorts of AGYW aged 13-22, followed since 2017/18, we estimated the impact of DREAMS on social support and self-efficacy by 2022. With a nested sample of cohort participants in 2022, we conducted qualitative inquiry through in-depth interviews and participatory action learning with DREAMS participants, implementers, and community members, for evidence of mechanisms, achievement and contextual influences on AGYW empowerment. We found statistical evidence of a causal impact of DREAMS on social support and self-efficacy among adolescent girls. Qualitatively, DREAMS enhanced AGYW's access to and control of resources, including coveted material assets like educational subsidies, hygiene products, and business support, which reportedly reduced transactional sex through economic autonomy and bodily integrity. DREAMS enhanced intangible resources like HIV knowledge and financial skills. Greater confidence, courage, and critical consciousness enabled some AGYW to act on health choices, assume leadership roles, and continue education. In mentor-led activities, AGYW demonstrated collective action and solidarity and group saving skills for financial autonomy. DREAMS aimed to engage the broader community including leaders, parents, and young men, but social structures, dominant gender norms, gender-based violence, and widespread poverty mitigated its empowering impact for AGYW. We found compelling evidence that DREAMS strengthened many young women's access to and control of resources and their intrinsic and collective agency. These are important precursors to empowerment but insufficient for the transformation of power relations without supportive institutional structures, including gender-equitable norms and viable livelihood strategies.